Asma Ul Husna interactive courseware: adaptation of multimedia learning principles / Arifah Fasha Rosmani, Ray Adderley JM. Gining and Asiraa Angwar - Rosmani, Arifah Fasha; JM. Gining, Ray Adderley; Angwar, Asiraa (UiTM Cawangan Perlis, 2017)
Asma Ul Husna interactive courseware has been developed as an assistive tool intended for primary school students to learn about the 99 names of Allah SWT. The interactive courseware implemented multimedia elements such as text, graphic, audio and animation to assist users' learning process. Additionally, as it is presented with the absence of the traditional face-to face method, the materials are required to be engaging to the users. The 'engaging' requirement is achieved by adopting several multimedia learning principles. The principle of multimedia learning consists of variety of principles which are utilised to develop the design and organisation of multimedia presentations. User Acceptance test has been carried out among primary school students to determine the overall level of acceptance and understanding towards the courseware. Other than that, this test is also conducted to assess the effects of the multimedia learning principles being adopted. The impacts shown by the results are significant as to confirm its benefits to its target users.